THE EFFECT OF HEALTH WORKERS' COMPULSORY CITIZENSHIP BEHAVIOUR ON SERVICE PROCESS SABOTAGE BEHAVIOUR: THE PARALLEL MEDIATING ROLE OF SOCIAL LOAFING AND SUPERFICIAL ROLE-PLAYING (Third Sector Social Economic Review, 2024)
This study was designed to reveal the parallel mediating role of social loafing and superficial role-playing behaviours in the relationship between health care workers' obligatory citizenship behaviours and their tendency to sabotage service processes. For this purpose, the employees of a medium-sized training and research hospital located in the Eastern Anatolia region of Turkey were taken as the sample. Data were collected from 400 healthcare professionals by convenience sampling method. For the research data, scales whose validity and reliability have been tested in the literature were used. This study, in which quantitative data collection method was used, was also designed as descriptive, correlational and cross-sectional. When the research findings were evaluated, it was found that there were significant positive relationships between health care workers' compulsory citizenship behaviours and their behaviours of sabotaging service processes, social loafing tendencies and superficial role playing; significant positive relationships between social loafing tendencies and superficial role playing tendencies and behaviours of sabotaging service processes; and a significant positive relationship between superficial role playing tendencies and acts of sabotaging service processes. In addition, it was found that social loafing and superficial role-playing behaviours have a mediating role separately in the relationship between health care workers' obligatory citizenship behaviours and their tendency to sabotage service processes. Finally, it was also found that social loafing and superficial role-playing behaviours have a parallel mediating role in the relationship between health care workers' obligatory citizenship behaviours and their tendency to sabotage service processes.
Keywords: Compulsory citizenship; sabotaging service processes; social loafing; superficial role-playing; healthcare workers